Productivity of Fodder Maize (Zea mays L.) SFM-1 under Varied Sowing Dates and Nitrogen Levels - Nisar, Saima; Rashid, Zahida; Touseef, A.; Kumar, Rajneesh; Nissa, Seerat Un; Faheem, J.; A., Angrez; Sabina, N.; Shabeena, M.; Tanveer, A.; et al. (International Journal of Bio-resource and Stress Management, 2024)
This field experiment was carried out at Faculty of Agriculture, Wadura, Sher-e-Kashmir University of Agricultural Sciences & Technology of Kashmir during (April-October) kharif, 2022. The experiment was laid out in the split-plot design with four sowing dates (15th April, 15th May, 15th June and 15th July) and four nitrogen levels (0, 60, 120 and 180 kg ha-1) with three replications to study the effect of sowing dates and levels of nitrogen on growth, biomass, yield, quality and the nitrogen use efficiency of fodder maize. The growth parameters viz., plant height, leaf area index, number of leaves per plant were significantly influenced by varying sowing dates and nitrogen levels and higher values of these parameters were obtained with early sowing of 15th April. The dry matter accumulation, number of leaves per plant and green fodder yield were significantly higher at early sowing of 15th April. The maximum crude protein content (%) and ash content (%) were also recorded with sowing on 15th April. In case of nitrogen levels, the growth, yield and quality parameters viz., plant height, leaf area index, leaf stem ratio, number of leaves per plant, dry matter yield, green fodder yield, dry fodder yield, crude protein and ash content were significantly improved up to nitrogen level N3. However, NDF (%) and ADF (%) decreased with an increase in nitrogen levels and was lowest at N3 level.